If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -0.66) = -18 Reorder the terms: 4(-0.66 + x) = -18 (-0.66 * 4 + x * 4) = -18 (-2.64 + 4x) = -18 Solving -2.64 + 4x = -18 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2.64' to each side of the equation. -2.64 + 2.64 + 4x = -18 + 2.64 Combine like terms: -2.64 + 2.64 = 0.00 0.00 + 4x = -18 + 2.64 4x = -18 + 2.64 Combine like terms: -18 + 2.64 = -15.36 4x = -15.36 Divide each side by '4'. x = -3.84 Simplifying x = -3.84
| 4k-7=k-10 | | -24+10=m-5 | | 7x-35=-2(-8x+4) | | 15=5-n | | 17=-5 | | 8x+1=-16 | | -6x+4(x-4)=-14 | | 72c=8 | | 26-(x-11)=-5(x+7) | | 5m+2m-5= | | x/-13=-40 | | w=2x^2-yz | | y=0.5x+1.5 | | 14*30+d=-196 | | (4+1)+2= | | 8y+2=21 | | 14+30+d=-196 | | 3=x(9-2x)(6-2x) | | 20=s-5 | | 7x+9+3x+1=8x-5 | | 8x-11=-5 | | 4/5n-7=17 | | 4log(x)-log(x^4)= | | 2(3x-2)=10x-13-7x | | 2x^3+3x^2-8x-4=0 | | 2n+-3n+-14=0 | | 4m-9=11 | | 9x-4=4x+27 | | 2(-5x-7)=16 | | 2[-(2+13)+11]=2(x+2) | | -7(2x-3)=28 | | .6-0.25f=f-3 |